How to differentiate tany = ((3x-x^3)/(1-3x^2)) ?
tany = ((3x-x^3)/(1-3x^2))
2 Answers
Explanation:
I assume we're differentiating with respect to
d/dxtany=d/dx((3x-x^3)/(1-3x^2))
On the left, we need to use the chain rule. On the right, we'll use the quotient rule.
sec^2y(dy/dx)=((d/dx(3x-x^3))(1-3x^2)-(3x-x^3)(d/dx(1-3x^2)))/(1-3x^2)^2
Finding these derivatives and simplifying:
sec^2ydy/dx=((3-3x^2)(1-3x^2)-(3x-x^3)(-6x))/(1-3x^2)^2
sec^2ydy/dx=(3x^4+6x^2+3)/(1-3x^2)^2
You may notice the simplification:
sec^2ydy/dx=(3(x^2+1)^2)/(1-3x^2)^2
Now, we solve for the derivative:
dy/dx=1/sec^2y(3(x^2+1)^2)/(1-3x^2)^2
It's weird to leave the answer in this form, but we have a way around it! Recall that
dy/dx=1/(tan^2y+1)(3(x^2+1)^2)/(1-3x^2)^2
And we know that
dy/dx=1/((3x-x^3)^2/(1-3x^2)^2+1)(3(x^2+1)^2)/(1-3x^2)^2
Let's simplify that:
dy/dx=(1-3x^2)^2/((3x-x^3)^2+(1-3x^2)^2)(3(x^2+1)^2)/(1-3x^2)^2
Cancel the
dy/dx=(3(x^2+1)^2)/(x^6+3x^4+3x^2+1)
Which can be simplified:
dy/dx=(3(x^2+1)^2)/(x^2+1)^3
dy/dx=3/(x^2+1)
Explanation:
Recall that,
So, if we subst.
readily derived!